The Changing Political Structure of Europe : Aspects of International Law - Fitzmaurice, Malgosia,; Lefeber, René,; Vierdag., E.W., (International Law - Book Archive pre-2000., 1991)
Following profound modifications of Soviet ideology after the coming to power of Gorbachev, Europe experienced an unprecedented time of change which resulted, inter alia, in the unification of the two German States, the abolition of socialist international organizations, the obsolescence of neutrality policies in the New Europe and the pull on the European Communities to admit new members. These revolutionary events give rise to interesting legal questions. Since international relations are changing, the legal framework in which these relations are set has to change, too. In December 1990, international legal aspects of the changes in the political structure of Europe were discussed at a conference held in Amsterdam. In this book, which takes account of the outcomes of the discussions, the international legal framework in which these changes take place and their consequences are described and analyzed by eminent scholars from East and West.